Comparison of resting heart rate and blood pressure between professional and amateur women bharathanatyam dancers. - Sabaananth, S.; Gopinath, V. (My University, 2012)
The purpose of this study was to compare resting heart rate and blood pressure between professional and amateur Bharathanatyam dancers. To achieve the purpose sixty (N=60) women Bharathanatyam dancers were selected and they were classified in to Professional Dancers [(PD) (n=30, practice bharathanatyam 90 to 120 min / day for 5 to 6 day / week over the period of minimum 5 years)] and Amateur Dancers[(AD)( n=30, practice bharathanatyam 30 to 60 min / day/ 2 to 3 day / week over the period of minimum 5 years)] were selected as subjects, their mean age were 17 ± 1.3 years. They were measured resting heart rate using Palpating the radial artery for full one minute for each subject and blood pressure using Standardized sphygmomanometer and stethoscope. The resting heart rate and blood pressure were taken during early morning hours the collected data were statistically treated by using independent‘t’ test , 0.05 level of confidence was fixed to test the significance. The result shows that Professional Dancers were lesser than Amateur Dancers on RHR, SBP, and DBP. Hence it was concluded that, professional bharathanatyam dancers have lower RHR, SBP, and DBP than amateur dancers.
Keywords: RHR; SBP; DBP; Professional Dancers; Amateur Dancers; Bharathanatyam